Multiple cryptic species of sympatric generalists within the avian blood parasite Haemoproteus majoris. (27th June 2016) - Nilsson, E.; Taubert, H.; Hellgren, O.; Huang, X.; Palinauskas, V.; Markovets, M. Y.; Valkiūnas, G.; Bensch, S.
Abstract: The avian haemosporidian parasite Haemoproteus majoris has been reported to infect a wide range of passerine birds throughout the Holarctic ecozone. Five cytochrome b (cyt b ) lineages have been described as belonging to the morphological species H. majoris, and these form a tight phylogenetic cluster together with 13 undescribed lineages that differ from each other by < 1.2% in sequence divergence. Records in a database (MalAvi) that contains global findings of haemosporidian lineages generated by universal primers suggest that these lineages vary substantially in host distribution. We confirm this pattern in a data set collected at Lake Kvismaren, Sweden, where three of the generalist lineages have local transmission. However, whether these lineages represent intraspecific mitochondrial diversity or clusters of cryptic species has previously not been examined. In this study, we developed novel molecular markers to amplify the partial segments of four nuclear genes to determine the level of genetic diversity and gene phylogenies among the five morphologically described cyt b lineages of H. majoris . All five cyt b lineages were strongly associated with unique nuclear alleles at all four nuclear loci, indicating that each mitochondrial lineage represents a distinct biological species. Within lineages, there was no apparent association between nuclear alleles and host species, indicating that they form genetically unstructured populations across multiple host species.